Pathology [videorecording (DVD)] - Lucchesi, Gary; Neveldine, Mark; Taylor, Brian; Williamson, Skip; Schölermann, Marc; Ventimiglia, Milo, 1977-; Weston, Michael, 1973-; Smith, Lauren Lee, 1980-; Whitworth, Johnny, 1975-; De Lancie, John, 1948-; Milano, Alyssa (Metro-Goldwyn-Mayer : Distributed by Twentieth Century Fox Home Entertainment, 2008)
A top med school student enters into a deadly game with a group of pathology interns. He becomes a pawn in their dangerous and secret after-hours game at the morgue of who can commit the perfect undetectable murder.